2003
DOI: 10.1029/2003jd003582
|View full text |Cite
|
Sign up to set email alerts
|

Toward aerosol/cloud condensation nuclei (CCN) closure during CRYSTAL‐FACE

Abstract: [1] During July 2002, measurements of cloud condensation nuclei were made in the vicinity of southwest Florida as part of the Cirrus Regional Study of Tropical Anvils and Cirrus Layers-Florida Area Cirrus Experiment (CRYSTAL-FACE) field campaign. These observations, at supersaturations of 0.2 and 0.85%, are presented here. The performance of each of the two CCN counters was validated through laboratory calibration and an in situ intercomparison. The measurements indicate that the aerosol sampled during the cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
114
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 40 publications
(66 reference statements)
2
114
1
1
Order By: Relevance
“…In a significant number of prior closure studies, modeled CCN concentrations were larger than measured, although generally within uncertainty limits (Martin et al 1994;Snider and Brenguier 2000;Chuang et al 2000;Covert et al 1998;Zhou et al 2001;Cantrell et al 2001;Snider et al 2003;Dusek et al 2003;Roberts et al 2002;VanReken et al 2003;Rissler et al 2004). The positive model bias also increased for moderate to highly polluted conditions.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a significant number of prior closure studies, modeled CCN concentrations were larger than measured, although generally within uncertainty limits (Martin et al 1994;Snider and Brenguier 2000;Chuang et al 2000;Covert et al 1998;Zhou et al 2001;Cantrell et al 2001;Snider et al 2003;Dusek et al 2003;Roberts et al 2002;VanReken et al 2003;Rissler et al 2004). The positive model bias also increased for moderate to highly polluted conditions.…”
Section: Introductionmentioning
confidence: 83%
“…Cantrell et al (2001) found good general agreement between the measured and predicted CCN for marine aerosol sampled during the Indian Ocean Experiment (INDOEX) field program; however, the modeled CCN overpredicted observed CCN number concentration for one specific period when organic carbon was greater than 25% of total aerosol mass. VanReken et al (2003) found that an idealized composition of pure (NH 4 ) 2 SO 4 yielded good aerosol-CCN closure during the Cirrus Regional Study of Tropical Anvils and Cirrus Layers: Florida Area Cirrus Experiment (CRYSTAL FACE) for all flights with the exception of one. For this particular flight, CCN was elevated in concentration and back trajectories originated from the polluted boundary layer over Georgia several days earlier.…”
Section: Introductionmentioning
confidence: 94%
“…A higher concentration of CCN at a given supersaturation will lead to more droplets with a smaller mean droplet diameter. This may lead to a more reflective cloud and is termed the first indirect effect, or Twomey effect (Twomey, 1977). The second indirect effect is related to the inhibition of precipitation in clouds with small mean droplet diameters which affects the extent and lifetime of clouds (Albrecht, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…For example, different closure studies have relied on CCN concentrations determined through direct counting of the subset of an aerosol that activates at the peak supersaturation, S p , in the chamber (VanReken et al 2003), through measurement of the difference in concentration of a sampled aerosol before and after gravitational removal of all CCN (Cantrell et al 2001), through measurement of the droplet size distribution at equilibrium at 100% RH (Liu et al 1996), and through a calibration-based relationship between S c and droplet size in a CCN spectrometer (Gasparini et al 2006). Additionally, different investigators employ varied techniques to relate the aerosol data to CCN concentrations.…”
Section: Introductionmentioning
confidence: 99%